Penentuan Cadangan Asuransi Jiwa Last Survivor berdasarkan Metode Gross Premium Valuation (GPV) dengan Hukum De’Moivre - Rhanny Kirana Jefri; Sri Dewi Anugrawati; Nurwahidah Nurwahidah (Eigen Mathematics Journal, 2026)
Insurance is one of the measures that can be used to prepare for various risks that can occur at any time. In the context of life insurance products, multiple life insurance is an efficient option because it is more economical than purchasing separate policies for two people with equivalent benefits. Unlike previous studies that focused on single life models using the GPV (Gross Premium Valuation) approach, this study develops an analysis of more complex multiple life insurance products, thereby providing a more representative picture of premium reserves for cases involving two insured parties. This study aims to formulate a mathematical model and conclude the results of prospective premium reserve calculations for last survivor whole life insurance using the GPV (Gross Premium Valuation) approach and De'Moivre's law De’Moivre This study uses a quantitative method with a documentation data collection technique, namely the 2019 Mortality Table IV data published by the Indonesian Life Insurance Association (AAJI). The results of this study show that the mathematical model of premium reserves for last survivor whole life insurance using the GPV (Gross Premium Valuation) approach and De'Moivre's law is ${_t}V^{GPV} = BA_{\bar{xy}} + U + PAG_{\bar{xy}} + A{\ddot{a}}_{\bar{xy}} + CA_{\bar{xy}} - G_{\bar{xy}}{\ddot{a}}_{\bar{xy}}$. However, when the insured ($y$) dies first, the mathematical model is ${_t}V^{GPV} = BA_{\bar{x}} + U + PAG_{\bar{xy}} + A{\ddot{a}}_{\bar{x}} + CA_{\bar{x}} - G_{\bar{xy}}{\ddot{a}}_{\bar{x}}$ while if the insured ($x$) dies first, the mathematical model is ${_t}V^{GPV} = BA_{\bar{y}} + U + PAG_{\bar{xy}} + A{\ddot{a}}_{\bar{y}} + CA_{\bar{y}} - G_{\bar{xy}}{\ddot{a}}_{\bar{y}}$. In addition, the results of the study show that there is a difference in the last survivor life insurance premium reserve between the conditions when both insured persons are still alive and when one of them dies, and that the use of De'Moivre's law results in a decreasing reserve pattern but ends up exceeding the promised benefits due to linear mortality assumptions so that the present value of the benefits does not fully decrease at the end of the coverage period. These findings indicate that the use of a uniform death distribution needs to be considered in order to produce more realistic premium reserves.